An umpolung strategy for rapid access to thermally activated delayed fluorescence (TADF) materials based on phenazine. Issue 10 (12th January 2022) - Zhang, Huaxing; Guo, Qiang; Cheng, Hu; Ran, Chunhao; Wu, Di; Lan, Jingbo
Abstract : Ag(I)-promoted regioselective intramolecular radical nucleophilic addition/rearrangement of 2-aryl diazaboroles has been accomplished to construct phenazine structures, which is an umpolung strategy based on the classical electrophilic mechanism. Abstract : Herein, Ag(I)-promoted regioselective intramolecular radical nucleophilic addition/rearrangement of 2-aryl diazaboroles has been accomplished for the first time to construct phenazine structures. This protocol is an umpolung strategy based on the classical electrophilic mechanism, and therefore, a reversed regioselectivity was observed, which provides an opportunity to prepare sterically hindered phenazines. The resulting thermally activated delayed fluorescence (TADF) materials based on phenazine exhibit emission bands from green to red with high quantum yields and moderate fluorescence lifetimes as solid films.